(untitled) (Annals of Medical Research, 2021)
Aim: The research aimed to analyze the effect of job satisfaction level of nurses on their ethical sensitivity.Material and Methods: As a descriptive study, the research was performed at a training and research hospital in South East Turkey. Research population was composed of nurses working for this hospital whereas research sample was comprised of a total of 148 nurses agreeing to participate in the research in the hospital. Research data were collected between April and June 2017 through Nurse Information Form, Minnesota Satisfaction Questionnaire (MSQ) and the Ethical Sensitivity Questionnaire (ESQ).Results: It was ascertained that participants’ means of overall MSQ scores, intrinsic satisfaction scores and extrinsic satisfaction scores were respectively 51.91±11.28, 33.16±7.42 and 18.75±5.08. Besides, it was discerned that means of scores of overall ESQ and its sub-scales, autonomy, benevolence, holistic approach, conflict, practice and orientation, were respectively 91.55±21.66, 18.72±6.72, 13.00±4.50, 13.55±5.03, 12.81±3.73, 13.10±4.83 and 8.87±4.19. University graduates’ mean of overall MSQ scores was higher, and the difference in the mean of overall MSQ scores was found to be statistically significant. The difference in the mean of MSQ extrinsic satisfaction scores was found to be statistically significant on the basis of gender variable.Conclusion: It was found that job satisfaction of nurses was at normal level and their ethical sensitivity was at moderate level. It was found that there was a negative correlation between ESQ total and internal satisfaction, and MSQ total and autonomy subdimension.